A Paradigm Shift in Identity: Conceptualizing Passwordless Authentication using Hashgraph Technology - Navarro, Christopher Edmund Baligod; Leonen, Jeffrey T. (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose   – This concept paper uniquely explores the novel application of hashgraph technology in the passwordless authentication realm. Hashgraph algorithm is known for its performance, stability, and security. It achieves the gold standard for security by differentiating itself by focusing on integrating asynchronous Byzantine Fault Tolerance (aBFT) and the gossip protocol for enhanced resilience and scalability. Unlike existing discussions, this study highlights how hashgraph’s unique attributes overcome key challenges in digital identity management, providing a paradigm shift from traditional and even next-generation authentication methods. Method – This study will synthesize current literature and technological advancements in both passwordless authentication and distributed ledger technologies (DLTs). Conclusion – Hashgraph technology offers a groundbreaking approach to passwordless authentication, effectively addressing the limitations of traditional and next-generation methods. Its features—such as asynchronous Byzantine Fault Tolerance (aBFT), the gossip protocol, and decentralized identifiers (DIDs)—make it highly secure, scalable, and user-friendly. By removing dependency on passwords, this approach enhances both privacy and resilience against digital attacks. This paradigm shift can lead to more robust and structured digital identity systems, rethinking cybersecurity standards. Recommendations – To fully realize the potential of hashgraph in passwordless authentication, it is essential to develop a prototype to validate the proposed framework and conduct large-scale testing to assess its scalability and real-world reliability. Developing a seamless integration of this technology with existing authentication systems and ensuring compatibility with current platforms will be critical to driving adoption. Moreover, user awareness campaigns must address potential resistance to change and promote understanding of the potential benefits of this technology. Research Implications – This study on passwordless authentication using hashgraph technology has significant implications for the future of digital identity management, offering enhanced security and user experience while promoting decentralized identity systems across various sectors. Vital areas for further research include addressing integration challenges, user adoption, data privacy concerns, and the technology's potential in an evolving cybersecurity landscape. Practical Implications – Hashgraph-based authentication offers significant practical benefits, including enhanced security, reduced operational costs, and an improved user experience with seamless, privacy-centric processes. The properties like low latency and scalability will make it ideal for large-scale applications, potentially reshaping cyber security and digital identity standards for a more secure and user-focused.